Strategi Kebijakan Pembangunan Daerah Berbasis Pertanian dan Sosial Ekonomi di Kabupaten Enrekang - M, Nursafitra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
This study aims to analyze the regional development policy strategy in Enrekang Regency with a focus on the agricultural sector and the socio-economic resilience of the community, which has strong relevance to the Resilience Theory in Rural Development because it is able to describe the factual conditions and the direction of development needed in rural areas that depend on the agricultural sector. Enrekang Regency is known as a center for horticultural production, but still faces challenges in the form of price fluctuations and dependence on middlemen. The research methods used are literature review, observation, and review of regional policy documents. The results of the study indicate that the development policy strategy is directed at strengthening the agricultural sector based on local potential, improving infrastructure and accessibility, and empowering communities through farmer institutions. Although there have been efforts to improve and implement policies, especially in terms of price stabilization and market strengthening. The conclusion of this study confirms that the regional development policy strategy in Enrekang Regency with a focus on the agricultural sector and socio-economic resilience in Enrekang Regency has been implemented well, however, the success of development in Enrekang Regency is greatly influenced by the synergy between the government, the community, and local institutions. Research recommendations suggest the need to strengthen regional marketing institutions, increase infrastructure investment, and provide intensive training for farmers to enable them to adapt to market dynamics and sustainable agricultural technologies.